Assessment of the overall condition of bridge decks using the Jensen-Shannon divergence of NDE data. (March 2020) - Rashidi, M.; Azari, H.; Nehme, J.
Abstract: This paper presents the successful application of the Jensen-Shannon divergence (JSD) for the overall condition assessment of bridge deck structures using nondestructive evaluation (NDE) data. Periodic (time-lapsed) results from electrical resistivity, half-cell potential, ground penetrating radar, ultrasonic surface wave, and impact-echo measurements on the Haymarket Bridge deck (located in Virginia, U.S.) are represented in the form of probability distributions, and the deviation from original distributions is calculated using the square root of the Jensen-Shannon divergence ( J S D ). The effects of bin size on the probability distribution, and of instruments varying in resolution on J S D are discussed. Finally, by assuming ideal probability distributions representing an intact condition of the bridge deck, an NDE index for condition assessment of bridge decks is suggested and deterioration curves are developed. Results demonstrate the effectiveness of J S D to evaluate relative changes in the bridge deck condition.